2020
DOI: 10.3390/jmse8121032
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Sediment Selection by the Mud Shrimp Upogebia noronhensis (Crustacea: Thalassinidea) and the Potential Effects on the Associated Macroinfaunal Community

Abstract: Burrowers such as thalassinideans remobilize sediment in benthic ecosystems, altering granulometry, enhancing organic matter cycling and oxygenation. We characterized the distribution of the mud shrimp Upogebia noronhensis and the associated macroinfauna along a depth and granulometric gradient in a shallow subtidal area in the southern Brazilian coast. Mud shrimp densities were estimated by burrow opening count using 0.25 m2 quadrats in three sediment zones: sand, sand-mud transition and mud. Macroinfaunal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…These data indicate that the mantis shrimps were selective in the materials they used to construct their burrows, in particular the inner wall lining. Grain size selectivity in burrow construction has been reported in several burrowing marine invertebrates including crustaceans (Sumida et al, 2020;Zorn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that the mantis shrimps were selective in the materials they used to construct their burrows, in particular the inner wall lining. Grain size selectivity in burrow construction has been reported in several burrowing marine invertebrates including crustaceans (Sumida et al, 2020;Zorn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The density of other Upogebia species in various regional seas typically ranges from 20 individuals/m 2 to over 200 individuals/m 2 . Although most studies reported U. africana (Ortmann, 1894) to have a high maximum density of 200 to 600 individuals/m 2 [86,[93][94][95][96], the maximum density of other Upogebia such as U. pusilla (Petagna, 1792) [87,97,98], U. omissa Gomes Corrêa, 1968 [30], U. pugettensis [34], and U. deltaura (Leach, 1816) [99] is generally reported to be around 100 to 140 individuals/m 2 . Therefore, the maximum density in our study was somewhat lower than that of U. africana, but higher than that of other Upogebia species.…”
Section: Shrimp Densitymentioning
confidence: 99%